Sex-Specific Association between Systolic Blood Pressure Time in Target Range and Cardiovascular Outcomes: A Post-Hoc Analysis of the SPRINT Trial - Yuekun Zhang; Wen Zheng; Chao Jiang; Wen Hao; Wei Gong; Yan Yan; Xiao Wang; Changsheng Ma; Shaoping Nie (Reviews in Cardiovascular Medicine)
Background: Systolic blood pressure time in target range (SBP TTR) is a novel metric for blood pressure control. Previous studies have demonstrated an inverse association between SBP TTR and risks of cardiovascular events, but sex differences have never been reported. This study aims to investigate the sex-specific differences in the relationship using data from the Systolic Blood Pressure Intervention Trial (SPRINT). Methods: This post hoc analysis included 8822 SPRINT participants with at least three follow-up systolic blood pressure (SBP) measurements within the first three months. SBP TTR was calculated using the Rosendaal method of linear interpolation. The primary endpoint was major adverse cardiovascular and cerebrovascular events (MACCE). Cox proportional hazards models and restricted cubic splines (RCS) were used to assess the association between SBP TTR and cardiovascular events. Results: Women accounted for 35.3% with a mean age of 68.6 ± 9.5 years, having a higher body mass index (p = 0.007) and a lower SBP TTR compared to men (p < 0.001). In the overall population and in women, each standard deviation (SD) increase in SBP TTR was associated with a reduced risk of MACCE (adjusted hazard ratio (HR) 0.89; 95% confidence interval (CI) 0.82–0.97; p = 0.007, and adjusted HR 0.85; 95% CI 0.74–0.99; p = 0.039, respectively) and acute decompensated heart failure (adjusted HR 0.86; 95% CI 0.73–0.99; p = 0.047, and adjusted HR 0.68; 95% CI 0.51–0.92; p = 0.011, respectively), while this was not observed in men. RCS indicated a similar trend in men only when SBP TTR exceeded 39%. Additional adjustments for mean SBP and SBP variability yielded similar outcomes. Conclusions: The study demonstrates that in women, a higher SBP TTR is associated with a reduced risk of MACCE and acute decompensated heart failure, while in men, a similar trend is observed only when SBP TTR is higher, underscoring the necessity of considering sex differences in personalized blood pressure management strategies. Clinical Trial Registration: NCT01206062, https://www.clinicaltrials.gov/expert-search?term=NCT01206062.